Contaminated land geotechnical remediation processes : the Institution of Civil Engineers, Ground Board, Ground Meetings Panel informal discussion : Wednesday 1st February 1995, 5.30-7.30pm - Johnson, Simon (Institution of Civil Engineers, 1995)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Minutes of an informal discussion held on 1 February 1995.